The Interference Mechanism of Basil Essential Oil on the Cell Membrane Barrier and Respiratory Metabolism of Listeria monocytogenes - Li, Changzhu; Zhang, Chenghui; Chen, Xiaochen; Cui, Haiying; Lin, Lin (Frontiers in Microbiology, 2022)
In order to prevent food-borne diseases caused by Listeria monocytogenes (L. monocytogenes) safely and effectively, plant essential oils that have no toxic side effects and are not prone to drug resistance have become the focus of research. This article takes basil (Ocimum basilicum L.) essential oil (BEO) as the research object and explores its antibacterial mechanism against L. monocytogenes. The site of action was preliminarily determined to provide a theoretical basis for the development of natural antibacterial agents. The results show that BEO has good antibacterial activity against L. monocytogenes. After 8 h of treatment with BEO (1mg/mL), the number of remaining bacteria reached an undetectable level. Combining spectroscopic analysis techniques (Raman, ultraviolet, fluorescence spectroscopy) and fluorescence microscopy imaging techniques, it was found that BEO increased the disorder of the hydrocarbyl chain of phospholipid tail, which in turn led to increased cell membrane permeability, thereby causing the leakage of intracellular proteins and DNA. Meanwhile, respiratory metabolism experiments showed that BEO inhibited the EMP pathway by inhibiting the activity of key enzymes. From the molecular docking results, this inhibition may be attributed to the hydrophobic interaction between α-bergamotene and the amino acid residues of phosphofructokinase and pyruvate kinase. In addition, BEO can also cause oxidative stress, and ROS may also be related to the damage of cell membranes and enzymes related to respiratory metabolism.